The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jpcc.0c03167
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional van der Waals Supramolecular Frameworks from Co-Hosted Molecular Assembly and C60 Dimerization

Abstract: A two-dimensional van der Waals supramolecular framework is created by self-assembled cocrystallization of C 60 and octanethiol molecules on the Au(111) surfaces. The framework is characterized by the two-dimensional C 60 network, in which the pores are filled by RS-Au-SR (R = CH 3 (CH 2 ) 7 S) staples. The framework is stabilized by cooperative interactions involving collective self-assembly instead of the commonly observed pairwise interactions between the nearest neighbors. The pairing of two adjacent C 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In a previous study, we observed the formation of porous C60 frameworks with OT filling the pores. 17 The C60/OT ratio can be changed by heating the sample up. The desorption temperature of OT is more than 200 K lower than that for C60, hence the coverage of OT can be reduced by gentle heating the sample with little effect on the coverage of C60.…”
Section: Results and Discussion (C60)7 Based Supramolecular Tilingmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we observed the formation of porous C60 frameworks with OT filling the pores. 17 The C60/OT ratio can be changed by heating the sample up. The desorption temperature of OT is more than 200 K lower than that for C60, hence the coverage of OT can be reduced by gentle heating the sample with little effect on the coverage of C60.…”
Section: Results and Discussion (C60)7 Based Supramolecular Tilingmentioning
confidence: 99%
“…In this image, one can see three distinct structures. i) Porous C60/OT framework 17 which occupies about 80% of the surface. ii) Pure striped phase of OT exhibiting parallel rows.…”
Section: Results and Discussion (C60)7 Based Supramolecular Tilingmentioning
confidence: 99%
See 2 more Smart Citations
“…The shapes of grown frameworks should be mainly influenced by the van der Waals interactions between the alkane chain and the C60 molecules. Gao, Pan, Guo, and coworkers investigated a two-dimensional van der Waals supramolecular framework consisting of C 60 molecules and octane thiol molecules on the Au(111) substrate by self-assembled co-crystallization method [119]. The porous framework was a result of cooperative self-organization with the C 60 molecule and octane thiol as cohosts of the framework, in which the pores were filled by RS-Au-SR (R = CH 3 (CH 2 ) 7 S) staples.…”
Section: Two-dimensional Nanoarchitecture From Fullerene With Other Componentmentioning
confidence: 99%